Emotional and Social Competencies and Their Relationship to the Professional Competencies of Future Preschool and Early Childhood Education Teachers - Estera Twardowska-Staszek; Barbara Surma; Irmina Rostek (Multidisciplinary Journal of School Education, 2024)
Research objectives and problem: Preparing to become a preschool and early childhood education teacher requires five years of academic training and many years of self-education. Success in the profession is not only ensured by strong academic performance and achievement of educational goals, but also by the development of emotional and social competencies, which are closely tied to professional competence. The goal of the study was to identify the relationships between emotional intelligence, social competence, and the self-assessment of professional competence among future preschool and early childhood education teachers.